Microsoft PowerPoint best practices, tips, and techniques : learn PowerPoint's advanced tools and features to create and deliver engaging presentations /: learn PowerPoint's advanced tools and features to create and deliver engaging presentations. (2023) - Bosse, Chantal
No abstract available